Bifidobacteria Was Decreased in Adult Patients With Irritable Bowel Syndrome Based on PCR and Bacterial Culture: A Systematic Review and Meta-Analysis - Bu, Zhibin; Ye, Xianghua; Huang, Bin; Liu, Rui; Peng, Ling (Turkish Journal of Gastroenterology, 2022)
The causes of irritable bowel syndrome remain unknown. Studies and meta-analyses revealed that intestinal microbiota disturbance was one of the causes of irritable bowel syndrome, but the results remained controversial. Therefore, we performed a systematic review and meta-analysis to identify the association between them. We performed a systematic meta-analysis of case–control studies from January 2000 to December 2020 to compare fecal microbes based on polymerase chain reaction and bacterial cul- ture between adult irritable bowel syndrome patients and healthy controls. The standardized mean difference value and a 95% CI were calculated. Two professional researchers used Newcastle–Ottawa Scale to reassess selected literature and extract high- quality studies. Six studies were included in our analysis. When all eligible studies were pooled into the meta-analysis, compared with healthy controls, the standardized mean differences of Bifidobacteria (standardized mean difference = −1.01, 95% CI =: −2.01 to −0.01) in irritable bowel syndrome patients decreased significantly, whereas the standardized mean differences of Enterococcus, Enterobacter, Lactobacillus, Bacteroides, and Escherichia coli did not change significantly in irritable bowel syndrome patients. However, heterogeneity was significant to perform sensitivity analysis and stratified analysis in all these special intestinal microbes. In summary, this study indicated that only Bifidobacteria was decreased in irritable bowel syndrome patients compared with healthy controls using Newcastle–Ottawa Scale standards to extract high-quality literature. Future studies are warranted to further dem- onstrate the relationship between them.